Combining Microfinance and Health in Reducing Poverty-Driven Healthcare Costs: Evidence From the Philippines - Aranas, Lolita L.; Khanam, Rasheda; Rahman, Mohammad Mafizur; Nghiem, Son (Frontiers in Public Health, 2020)
The role of microfinance in alleviating poverty and poor health is significant. Its health programs have been shown to improve healthcare utilisation and strengthen a healthcare system. In the Philippines, microfinance’s widespread presence is seen as instrumental in achieving the objectives of Healthy Philippines 2022, particularly in reducing poverty-driven healthcare costs. However, little is known on how microfinance can reduce the cost of healthcare services and treatment. Also, few studies that consider the practice of integrated microfinance and health programs in the Philippines are seen. Secondary data was used to explore the structure and function of microfinance and health initiatives and their influence in mitigating healthcare costs. A review criterion was developed to examine the data using the three key elements identified in the Ruducha and Jadhav framework: organisational arrangement, health products and health outcomes. Findings revealed that most health initiatives are delivered through partnerships and collaboration, favour a reduction in healthcare costs and protection from out-of-pocket health expenditure. They are designed to operate in three structures – subsidised or outreach, microinsurance and health loans, and patronage refunds. The cooperative’s business venture providing pharmaceuticals facilitated access to affordable medicine and offered its members financial viability. Health loans and microinsurance also offered healthcare cost reductions; however, uptakes are low. The study found no data to assess the output of the completed health initiatives. More studies that will evaluate the integrated MFI health initiatives are recommended to further identify gaps, outcomes or impacts of the program.